The role of social capital in the creation of sustainable livelihoods : a case study of the Siyazama Community Allotment Gardening Association (SCAGA) - Jacobs, Cindy (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Sociology and Social Anthropology))--University of Stellenbosch, 2009.